Porous ceramic substrate, preparation method thereof and application of porous ceramic substrate in gas sensor
By using a porous ceramic substrate in a fuel cell type H2 gas sensor, the catalyst is implanted into the ceramic, and the problems of large amount of catalyst and complex structure in the prior art are solved, thereby improving the sensor response performance and simplifying the structure.
Patent Information
- Application Number
- CN202411915235.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Among the existing fuel cell type H2 gas sensors, the Pt-C catalyst is used in large quantities and the structural design is complex, making it difficult to improve the sensor's response performance.
Porous ceramics are used as substrate material to implant the catalyst inside the porous ceramics, and the catalytic performance of the catalyst is improved by using their pores and high specific surface area, and the gas phase reaction is converted into bulk phase reaction.
The amount of Pt-C catalyst is reduced, the response sensitivity and speed of the sensor is improved, the structural design of the sensor is simplified, and the mass production is facilitated.
Smart Images

Figure CN119715728A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensing, and in particular to a porous ceramic substrate and a preparation method thereof and application in a gas sensor. Background Art
[0002] With the continuous development of materials science and sensing technology, the research on electrochemical gas sensors has also made significant progress. At present, fuel cell type H2 gas sensors have appeared on the market. They use catalysts to catalyze H2 to produce electrochemical reactions at the Nafion membrane. They do not contain electrolyte solutions, and the sensors have a longer life than liquid or semi-solid electrochemical gas sensors. The catalyst usually uses a high concentration of Pt-C catalyst and is attached to both sides of the Nafion membrane through a screen printing process, or by spraying the Pt-C catalyst onto carbon paper and then attaching it to both sides of the Nafion membrane. In order to maximize the response of the sensor, the amount of Pt used in the above methods is large, and the sensor needs to design a complex structure to filter other interfering gases and ensure the semi-closure of the sensor and the connection of the circuit. Summary of the invention
[0003] The purpose of the present invention is to provide a porous ceramic substrate and a preparation method thereof and an application in a gas sensor, implanting a catalyst into the porous ceramic, utilizing the pores and high specific surface area of the porous ceramic to improve the catalytic performance of the catalyst, reduce the amount of Pt-C catalyst, convert the gas phase reaction of the sensor from the Nafion surface to the bulk phase reaction, and improve the sensor response.
[0004] In one aspect of the present invention, the present invention provides a method for preparing a porous ceramic substrate. According to an embodiment of the present invention, the method comprises the following steps:
[0005] (1) dipping the ceramic sheet in a glucose solution, then taking it out to dry, and annealing it in a tube furnace;
[0006] (2) immersing the ceramic sheet obtained in step (1) in an aqueous solution of chloroplatinic acid, taking it out and drying it, then immersing it in an icy aqueous solution of sodium borohydride, and finally taking it out and drying it;
[0007] (3) Immersing the ceramic sheet obtained in step (2) into a Nafion solution, or spraying a prepared Nafion solution on the surface of the ceramic sheet, and then drying, to obtain the porous ceramic substrate.
[0008] In addition, a porous ceramic substrate according to the above embodiment of the present invention may also have the following additional technical features:
[0009] In some embodiments of the present invention, in step (1), the method for preparing the ceramic sheet comprises the following steps:
[0010] ① Add aluminum oxide, zinc oxide, iron oxide, magnesium oxide, chromium oxide, pore-forming agent, dispersant, and adhesive A into a ball mill, add appropriate amount of deionized water for ball milling, and then add adhesive B and plasticizer in sequence for continued ball milling;
[0011] ② The slurry after ball milling is dried to absolute dryness, ground into fine powder, sieved, dry molded and compressed, and then sintered and debonded to obtain ceramic sheets.
[0012] In some embodiments of the present invention, the weight of raw materials for preparing ceramic sheets is as follows: 6-8 parts of aluminum oxide, 1-2 parts of zinc oxide, 0.05-0.1 parts of iron oxide, 0.2-0.5 parts of magnesium oxide, 0.02-0.05 parts of chromium oxide, 1-1.5 parts of pore former, 0.1-0.2 parts of dispersant, 0.2-0.3 parts of adhesive B, 1.02-2.04 parts of adhesive A, and 0.38-0.63 parts of plasticizer.
[0013] In some embodiments of the present invention, the pore-forming agent is corn starch or carbon powder, the dispersant is polyethylene glycol 1800, the adhesive A is polyvinyl alcohol, the adhesive B is methyl cellulose, and the plasticizer is glycerol.
[0014] In some embodiments of the present invention, the ball milling speed is 400-600r / min, the first ball milling time is 1-5h, and the second ball milling time is 1-5h; the oven drying temperature is 60-70°C; the sieve is 200-400 mesh; the dry mold compression pressure is 20MPa, and the holding time is 1-2min; the sintering atmosphere is air, the heating rate is 3-5°C / min, and it is heated to 500-600°C for degumming for 1-3h, and then the temperature is continued to rise at a heating rate of 3-5°C / min. The sintering temperature is 1400-1600°C, the sintering time is 1-6h, and the temperature is naturally reduced.
[0015] In some embodiments of the present invention, the concentration of the glucose solution is 0.5-3g / mL; the temperature of the glucose solution during preparation is 70-80°C, and after it is reduced to 50-60°C, the ceramic sheet is placed therein for an immersion time of 5-8min; high-temperature furnace annealing uses a tubular furnace, N2 atmosphere, annealing temperature of 500-600°C, annealing time of 1-3h, and the ceramic surface resistance after high-temperature annealing is controlled to be less than 500kΩ.
[0016] In some embodiments of the present invention, in step (2), the concentration of the chloroplatinic acid aqueous solution is 50-500 mg / mL, and the immersion time is 1-2 h; the concentration of the sodium borohydride icy aqueous solution is 50-100 mg / mL, and the immersion time is 1-2 h.
[0017] In some embodiments of the present invention, in step (3), the concentration of the Nafion solution is 1-200 mg / mL, and the drying temperature is 60-70°C.
[0018] In another aspect of the present invention, the present invention provides a method for preparing a porous ceramic-based fuel cell type electrochemical gas sensor. According to an embodiment of the present invention, the method comprises the following steps: taking the pretreated Nafion membrane and the porous ceramic substrate prepared by the preparation method of the porous ceramic substrate, cutting them into required sizes, and assembling them into a sensor.
[0019] In addition, the method for preparing a porous ceramic-based fuel cell type electrochemical gas sensor according to the above embodiment of the present invention may also have the following additional technical features:
[0020] In some embodiments of the present invention, the pretreatment method is as follows: the Nafion membrane is pretreated in 3-5wt% hydrogen peroxide solution, 0.4-0.6mol / L H2SO4 and deionized water, respectively, the pretreatment temperature is 75-85°C, and the pretreatment time is 0.5-1h; the sensor includes an upper cover, a shell, a porous ceramic used as a working electrode and a counter electrode, a Nafion membrane and an electrode.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) The present invention uses porous ceramic as the base material, which has a porous structure and increases the contact area between the reaction electrode and the gas, thereby improving the sensitivity and response speed of the sensor.
[0023] 2) In the present invention, the sensor catalyst layer material is directly attached to the ceramic sheet by impregnation, without screen printing and spot coating, which is convenient for mass production. The large specific surface area of the porous ceramic can effectively reduce the amount of Pt used and improve the catalyst activity.
[0024] 3) The ceramics are doped with glucose and annealed to form activated carbon, which increases the conductivity of the ceramic substrate on the one hand, and can serve as a filter layer to adsorb interfering gases such as H2S and ethanol on the other hand. The non-polar H2 gas can pass through the ceramic smoothly and reach the reaction interface for reaction.
[0025] 4) The different concentrations of chloroplatinic acid solutions in the present invention may cause the distribution and morphology of platinum on the ceramic surface to change, thereby affecting the selectivity of the catalyst. By adjusting the concentration of chloroplatinic acid, the selectivity of the catalyst can be optimized, making the ceramic more suitable for a specific catalytic reaction.
[0026] 5) When the catalyst is attached in the present invention, different types of catalysts can be obtained by changing the aqueous solution in which the catalyst is immersed, thereby achieving selective catalysis of different reaction pathways.
[0027] In summary, the present invention introduces porous ceramics, implants catalysts into the porous ceramics, utilizes the pores and high specific surface area of the porous ceramics to improve the catalytic performance of the catalyst, reduces the amount of Pt-C catalyst, converts the gas phase reaction of the sensor from the Nafion surface to the bulk phase reaction, and improves the sensor response. The performance of the sensor can be improved by adjusting the preparation process of the porous ceramics, optimizing the selection of electrode materials and structural design, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the structure of a porous ceramic-based fuel cell type H2 gas sensor according to an application example of the present invention;
[0029] In the figure, 1. upper cover, 2. outer shell, 3. Nafion membrane, 4. electrode, 5. air vent, 6. working electrode porous ceramic, 7. counter electrode porous ceramic, 8. Nafion layer on ceramic surface.
[0030] Figure 2 This is a diagram showing the response of a porous ceramic-based fuel cell type H2 gas sensor to H2 according to an application example of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing a porous ceramic substrate comprises the following steps:
[0034] Step 1: Ceramic Sheet Preparation
[0035] (1) Weigh 8 g of aluminum oxide, 2 g of zinc oxide, 0.1 g of iron oxide, 0.5 g of magnesium oxide, 0.05 g of chromium oxide, 1.5 g of carbon powder (pore former), 0.2 g of polyethylene glycol (dispersant) 1800 and 2 mL of polyvinyl alcohol (binder A) in a ball mill, add an appropriate amount of deionized water as a mixed solvent, and ball mill for 5 h at a speed of 600 r / min. Then, add 0.3 g of methyl cellulose (binder B) and 0.4 mL of glycerol (plasticizer) in turn and continue ball milling for 5 h.
[0036] (2) The ball-milled slurry is placed in an oven at 70°C and dried until absolutely dry, then ground into fine powder and passed through a 200-mesh sieve, the powder is placed in a mold, and molded under a pressure of 20 MPa for 1 min. The prepared embryo is placed in a muffle furnace, heated to 500°C at a heating rate of 3°C / min in an air atmosphere for degumming for 1 h, then continued to be heated to 1500°C at the same heating rate for constant temperature sintering for 1 h, and then taken out after natural cooling to obtain a ceramic sheet.
[0037] Step 2: The ceramic sheet is doped with glucose and annealed to form activated carbon, which can increase the conductivity of the ceramic substrate and can also be used as a filter layer to adsorb interfering gases such as H2S and ethanol. It is then immersed in a solution to allow the catalyst to adhere to the ceramic sheet. The specific preparation method is as follows:
[0038] (3) Weigh 3 g of glucose and 2 mL of deionized water into a beaker, heat the solution to 80 °C and stir to completely dissolve the glucose, then lower the temperature to 60 °C, place the ceramic sheet in the solution, soak for 8 min, take it out and place it on filter paper to dry, then place it in a tubular furnace, and heat it to 500 °C at a heating rate of 1 °C / min in a N2 atmosphere for annealing for 2 h. After high-temperature annealing, the surface resistance of the ceramic sheet is controlled to be less than 500 kΩ.
[0039] (4) Prepare a 500 mg / mL aqueous solution of chloroplatinic acid, add the above ceramic piece into 500 uL of the aqueous solution of chloroplatinic acid, soak for 2 hours, then take out and dry; prepare a 50 mg / mL aqueous solution of sodium borohydride on ice, take out 10 mL, add the dried ceramic piece into it, reduce the chloroplatinic acid in the ceramic piece, soak for 1 hour, then take out and dry.
[0040] Step 3: Nafion solution spraying
[0041] (5) The ceramic sheet prepared above was immersed in a 200 mg / mL Nafion solution, and then dried in an oven at 70° C. for later use, thereby obtaining a porous ceramic substrate.
[0042] Example 2
[0043] Compared with Example 1, the difference of this embodiment is that the concentration of indium chloride salt is 100 mg / mL, the solubility of chloroplatinic acid aqueous solution is 50 mg / mL, and other relevant parameters and steps are the same as those in Example 1.
[0044] Example 3
[0045] Compared with Example 1, the difference of this embodiment is that the concentration of the Nafion solution is 100 mg / mL, and other relevant parameters and steps are the same as those of Example 1.
[0046] Application Examples
[0047] A method for preparing a porous ceramic-based fuel cell type H2 gas sensor comprises the following steps:
[0048] (1) Before the experiment, the Nafion membrane was heated in 5 wt% hydrogen peroxide solution, 0.5 M H2SO4 and deionized water at 80°C for 1 h to remove organic impurities and protonate the Nafion. The pretreated Nafion membrane and ceramic sheet were cut into 0.5 cm × 0.5 cm and 0.8 cm × 0.5 cm squares.
[0049] (2) Sensor assembly. The structure of the sensor is as follows: Figure 1 As shown, the sensor includes an upper cover 1, a shell 2, a porous ceramic prepared in Example 1, a Nafion membrane 3 and an electrode 4. The upper cover 1 of the sensor is provided with an air vent 5, and the working electrode porous ceramic 6 is 0.8cm×0.5cm in size. The counter electrode porous ceramic 7 is 0.5cm×0.5cm in size. A Nafion layer 8 is attached between the working electrode porous ceramic 6 and the counter electrode porous ceramic 7, and the working electrode porous ceramic 6, the Nafion membrane 3 and the counter electrode porous ceramic 7 are sequentially installed in the shell 2 from top to bottom. An electrode 4 is installed on the shell 2, and the electrode 4 is respectively connected to the working electrode porous ceramic 6 and the counter electrode porous ceramic 7, and the connecting ceramic sheet end of the spring pin is a spring end. The sensor shell 2 and the upper cover 1 are installed in a tight fit and epoxy sealing glue is applied to the connecting edge.
[0050] like Figure 2 As shown, the response current value of the prepared sensor gradually increases with the increase of H2 concentration. The sensor has a response value of about 486nA to 2050ppm H2, indicating that the sensor has the ability to respond to a specific concentration of H2.
[0051] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a porous ceramic substrate, characterized in that: The following steps are involved: (1) dipping the ceramic sheet in a glucose solution, then taking it out to dry, and annealing it in a tube furnace; (2) immersing the ceramic sheet obtained in step (1) in an aqueous solution of chloroplatinic acid, taking it out and drying it, then immersing it in an icy aqueous solution of sodium borohydride, and finally taking it out and drying it; (3) Immersing the ceramic sheet obtained in step (2) into a Nafion solution, or spraying a prepared Nafion solution on the surface of the ceramic sheet, and then drying, to obtain the porous ceramic substrate.
2. The method for preparing a porous ceramic substrate according to claim 1, characterized in that: In step (1), the method for preparing the ceramic sheet comprises the following steps: ① Add aluminum oxide, zinc oxide, iron oxide, magnesium oxide, chromium oxide, pore-forming agent, dispersant, and adhesive A into a ball mill, add appropriate amount of deionized water for ball milling, and then add adhesive B and plasticizer in sequence for continued ball milling; ② Dry the slurry after ball milling, grind it into fine powder, sieve it, compress it into shape with a dry mold, and then sinter and debond it to obtain a ceramic sheet.
3. The method for preparing a porous ceramic substrate according to claim 2, characterized in that: The weight parts of raw materials for preparing ceramic sheets are as follows: 6-8 parts of aluminum oxide, 1-2 parts of zinc oxide, 0.05-0.1 parts of iron oxide, 0.2-0.5 parts of magnesium oxide, 0.02-0.05 parts of chromium oxide, 1-1.5 parts of pore former, 0.1-0.2 parts of dispersant, 0.2-0.3 parts of adhesive B, 1.02-2.04 parts of adhesive A, and 0.38-0.63 parts of plasticizer.
4. The method for preparing a porous ceramic substrate according to claim 2, characterized in that: The pore-forming agent is corn starch or carbon powder, the dispersant is polyethylene glycol 1800, the adhesive A is polyvinyl alcohol, the adhesive B is methyl cellulose, and the plasticizer is glycerol.
5. The method for preparing a porous ceramic substrate according to claim 2, characterized in that: The ball milling speed is 400-600r / min, the first ball milling time is 1-5h, the second ball milling time is 1-5h, and the oven drying temperature is 60-70°C; The sieve used is 200-400 mesh; The dry mold compression pressure is 20MPa, and the holding time is 1-2min; The sintering atmosphere is air, the heating rate is 3-5°C / min, the temperature is increased to 500-600°C for debinding for 1-3h, and then the temperature is continued to be increased at a heating rate of 3-5°C / min, the sintering temperature is 1400-1600°C, the sintering time is 1-6h, and the temperature is naturally reduced.
6. The method for preparing a porous ceramic substrate according to claim 1, characterized in that: In step (1): The concentration of the glucose solution is 0.5-3g / mL; the temperature of the glucose solution during preparation is 70-80°C, and after the temperature is reduced to 50-60°C, the ceramic sheet is placed therein for an immersion time of 5-8min; the high-temperature furnace annealing adopts a tubular furnace, a N2 atmosphere, an annealing temperature of 500-600°C, and an annealing time of 1-3h, and the surface resistance of the ceramic is controlled to be less than 500kΩ after high-temperature annealing.
7. The method for preparing a porous ceramic substrate according to claim 1, characterized in that: In step (2), the concentration of the chloroplatinic acid aqueous solution is 50-500 mg / mL, and the immersion time is 1-2 h; the concentration of the sodium borohydride icy aqueous solution is 50-100 mg / mL, and the immersion time is 1-2 h.
8. The method for preparing a porous ceramic substrate according to claim 1, characterized in that: In step (3), the concentration of the Nafion solution is 1-200 mg / mL, and the drying temperature is 60-70°C.
9. A method for preparing a porous ceramic-based fuel cell type H2 gas sensor, characterized in that: The following steps are involved: The pretreated Nafion membrane and the porous ceramic substrate prepared by the method for preparing a porous ceramic substrate according to any one of claims 1 to 8 are cut into required sizes and assembled into a sensor.
10. The method for preparing a porous ceramic-based fuel cell type H2 gas sensor according to claim 9, characterized in that: The pretreatment method is as follows: the Nafion membrane is pretreated in 3-5wt% hydrogen peroxide solution, 0.4-0.6mol / L H2SO4 and deionized water respectively, the pretreatment temperature is 75-85°C, and the pretreatment time is 0.5-1h; The sensor comprises an upper cover, a shell, porous ceramics used as a working electrode and a counter electrode, a Nafion membrane and electrodes.
Citation Information
Patent Citations
Sensing element and preparation method thereof
CN111505084A
Platinum-based water treatment monatomic catalyst and preparation method thereof
CN113663724A
Membrane electrode assembly, preparation method of membrane electrode assembly, electrochemical gas sensor and application of electrochemical gas sensor
CN115791918A
Potential type hydrogen sensor and preparation method thereof
CN116930290A
The dog's foot fur removal mold
KR1020240069324A